Effect of acetazolamide for long-lasting paroxysmal dystonia in a patient with multiple sclerosis: a case report and review of literature - Hsieh PC (Dove Medical Press, 2013)
Pei-Chun Hsieh,1 Shu-Min Chen,1–3 Yao-Hong Guo,1 Ta-Shen Kuan,1,2 Wei-Jang Yen,1 Wen-Chen Chang,1 Yu-Ching Lin1–3 1Department of Physical Medicine and Rehabilitation, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan, Republic of China; 2Department of Physical Medicine and Rehabilitation, College of Medicine, National Cheng Kung University, Tainan, Taiwan, Republic of China; 3Medical Device Innovation Center, National Cheng Kung University, Tainan, Taiwan, Republic of China Abstract: Dystonia is a rare manifestation of multiple sclerosis (MS), but it always interferes with the functional performance and quality of life. We report a rare case of long-lasting paroxysmal dystonia associated with MS. The patient was a 40-year-old woman with relapsing- remitting MS for 6 years. During the latest attack of MS, she suffered from long-lasting paroxysmal dystonia in her left hand. Despite treatment with pulse high-dose intravenous methylprednisolone, interferon, and baclofen, along with occupational therapy, the dystonia persisted and significantly bothered her daily activities. Finally, she was treated with oral acetazolamide (250 mg, three times a day for 4 days), which was very effective for the control of her dystonia. The dystonic movement subsided without recurrence in a follow-up of 17 months. We advocate this effective and safe treatment for patients with paroxysmal dystonia associated with MS.  Keywords: multiple sclerosis, dystonia, acetazolamide, movement disorders, rehabilitation